Selectivity tuning options in hydrogenation of m-chloronitrobenzene to m-chloroaniline over mono- and bimetallic supported Pt catalysts - Mane, Rasika B.; Potdar, Aparna S.; Nadgeri, Jayprakash M.; Biradar, Narayan S.; Rode, Chandrashekhar V. (Industrial & Engineering Chemistry Research, 2012)
Supported monometallic (Pt, Ni,) and bimetallic (Ni-Pt) catalysts were prepared for the selective liquid phase hydrogenation of m-chlronitrobenzene to m-chloroaniline (m-CAN). It was found that the use of sodium carbonate as an additive substantially reduced the extent of dehydrohalogenation in the case of monometallic, 1% Pt/C catalyst, to give the highest selectivity of 96% to m-CAN. Ni-Pt bimetallic catalyst although showed almost complete selectivity (>99%) to m-chloroaniline; its activity was several fold lower than that of 1% Pt/C Na2CO3 system. However, compared with Ni monometallic catalyst, bimetallic Ni-Pt showed higher activity and selectivity due to the presence of electron rich surface metallic Pt stabilized by Ni having lower ionization potential compared with Pt.

Simultaneous glycerol dehydration and in situ hydrogenolysis over Cu-Al oxide under an inert atmosphere - Mane, Rasika B.; Rode, Chandrashekhar V. (Green Chemistry, 2012)
Among various catalysts screened, the Cu-Al oxide catalyst, prepared by a co-precipitation method, exhibited excellent activity for simultaneous glycerol dehydration and its hydrogenolysis without external hydrogen. Detailed characterization by XRD, XPS, HR-TEM, TPR, etc., showed evidence of Cu2+ in the form of CuO and CuAl2O4, along with Cu-0 and Cu1+ species, which are responsible for their multifunctional roles in glycerol APR, dehydration and hydrogenolysis reactions under inert conditions. This catalyst also presented consistent activity for a duration of 400 h for autogeneous hydrogenolysis of refined glycerol with 36% selectivity to 1,2-propanediol (1,2-PDO). Manipulating the temperature and feed flow rate conditions, meant that the selectivity to acetol and 1,2-PDO could be tailored as desired. Substantial enhancement in 1,2-PDO selectivity (75%) was achieved for an aqueous bio-glycerol feed over the same catalyst for 50 h of testing.